EVALUATING A POSTGRADUATE PROGRAM SUPPORT: A DUAL APPROACH USING REALIST EVALUATION AND CIPP MODEL FOR ACCREDITION ENHANCEMENT - Priskila Issak Benyamin (STT Bethel Indonesia Jakarta, 2024)
This research explores the effectiveness of a Graduate Program Support Program in enhancing the accreditation status by employing the Realist Evaluation and CIPP (Context, Input, Process, Product) Model Evaluation approaches. Addressing a research gap regarding the nuanced impact of support programs on postgraduate accreditation, this study combines qualitative document analysis, stakeholder interviews, and field observations. The research investigates how contextual factors and program elements influence the success of the support program in the complex landscape of postgraduate education. The primary research question focuses on understanding the interplay between the Realist Evaluation and the CIPP Model in evaluating and improving accreditation outcomes. The study aims to comprehensively understand the key elements contributing to the program's success. Findings reveal that the integrated approach successfully enhances accreditation by addressing program components and contextual nuances. Recommendations include tighter integration of program components, enhanced collaboration among stakeholders, and refinement of evaluation strategies. In conclusion, integrating the Realist Evaluation and the CIPP Model proves valuable in designing effective support programs for advancing postgraduate accreditation, offering insights that contribute significantly to the existing knowledge in educational program evaluation